2021
DOI: 10.3390/pathogens10070795
|View full text |Cite
|
Sign up to set email alerts
|

Modern Development and Production of a New Live Attenuated Bacterial Vaccine, SCHU S4 ΔclpB, to Prevent Tularemia

Abstract: Inhalation of small numbers of Francisella tularensis subspecies tularensis (Ftt) in the form of small particle aerosols causes severe morbidity and mortality in people and many animal species. For this reason, Ftt was developed into a bona fide biological weapon by the USA, by the former USSR, and their respective allies during the previous century. Although such weapons were never deployed, the 9/11 attack quickly followed by the Amerithrax attack led the U.S. government to seek novel countermeasures against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…A finding in keeping with several bioinformatics studies that have shown unexpected CoP for LVS and several vaccines against other infectious diseases [57]. We have recently made a batch lot of ∆clpB under GMP conditions [66] that will be used to conduct clinical trials sometime in 2022 or 2023. Thereafter, we will be able to directly compare human immune responses to vaccination with ∆clpB and LVS that could reveal either a common or unique CoP for these two vaccines.…”
Section: Supplementary Materialssupporting
confidence: 71%
“…A finding in keeping with several bioinformatics studies that have shown unexpected CoP for LVS and several vaccines against other infectious diseases [57]. We have recently made a batch lot of ∆clpB under GMP conditions [66] that will be used to conduct clinical trials sometime in 2022 or 2023. Thereafter, we will be able to directly compare human immune responses to vaccination with ∆clpB and LVS that could reveal either a common or unique CoP for these two vaccines.…”
Section: Supplementary Materialssupporting
confidence: 71%
“…The LVS wbtA mutant similarly used here has been described [50]. The clpB mutant of S4 [10] was provided by the National Research Council-Canada. The RML isolate of LVS was provided by Catharine Bosio.…”
Section: Bacteriamentioning
confidence: 99%
“…We engineered S4 vaccine candidates with unmarked deletions in genes (guaBA and aroD) encoding critical enzymes in biosynthetic pathways; similar mutations in the enteric pathogens Shigella and Salmonella Typhi resulted in promising vaccine strains that are safe, highly attenuated, and immunogenic for Hu in clinical trials [7][8][9]. Independently, the Conlan and Sjostedt groups developed and characterized a S4 vaccine candidate, S4∆clpB, which lacks a chaperone protein required for secretion of virulence factors (see [10] and references therein). All three S4-based vaccine candidates (S4∆clpB, S4∆guaBA, and S4∆aroD) have been tested for attenuation and vaccination efficiency (VE) in one or more rodent models (mice (Mo), guinea pigs, rats (Rt)) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations